The Experiences Surrounding Romantic Relationships of Korean Bisexual Individuals - Park, Jeongeun; Chung, Seojin (Frontiers in Psychology, 2023)
In recent years, the level of social and academic interest in sexual minorities has been gradually increasing. However, studies on bisexual individuals and the data on experiences of bisexual individuals outside the U.S. are scarce. To decrease the gap in the literature, this article examined the experiences of South Korean bisexual individuals in a context of romantic relationship via semi-structured, in-depth interviews. Participants were recruited through online based platforms and the interview from 8 participants were analysed. The five main themes were identified: discovering myself as bisexual, being exposed to discrimination and exclusion; being affected by the sex of a romantic partner; protecting myself when engaging in a romantic relationship, and benefits of romantic relationship. The findings suggest that Korea’s heteronormative system and culture were the major challenges perceived by the participants. In conclusion, this study illustrates how sociocultural norms, social acceptance and recognition affect bisexual identity in a romantic relationship.